Moisture-Dependent Thermal Properties of Cocoyam Cormels - Oyefeso, B. O.; Raji, A. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Cocoyam (Xanthosoma sagittifolium) has served as a cheap carbohydrate source for many people in the developing countries with prospects in the production of animal feed, lager beer, and its starch as binding agent in drug formulation. Drying is an important unit operation in cocoyam processing and there appears to be lack of information on the thermal properties which are significant in designing heat treatment systems such as dryers for the cormels. This study therefore, investigated some thermal properties of X. sagittifolium cormels as affected by moisture content. Thermal properties namely thermal conductivity, diffusivity and specific heat of white- and pink-fleshed cocoyam cormels were investigated at moisture contents within the ranges of 130 to 395% and 85 to 200% (dry basis), respectively. The selected thermal properties of the cormels were determined with the aid of a thermal properties analyser which has a dual needle probe and uses transient line heat source method. Thermal conductivity, diffusivity and specific heat were within the ranges of 0.454 to 0.562 Wm-1K-1, 1.62×10-7 to 2.32×10-7 m2s-1, 1.836to 4.029 kJkg-1K-1, respectively for white-fleshed cocoyam and 0.489 to 0.601 Wm-1K-1, 1.79×10-7 to 2.65×10-7 m2s-1, 1.615 to 2.991 kJkg-1K-1, respectively for pink-fleshed cormels. Analysis of variance showed that there were significant differences between the measured properties at different moisture content levels. Regression models were established between the investigated thermal properties and moisture content.